Chondrocytes-Specific Expression of Osteoprotegerin Modulates Osteoclast Formation in Metaphyseal Bone - Wang, Baoli (Sci Rep, 2015)
Bone marrow stromal cells/osteoblasts were originally thought to be the major player in regulating osteoclast differentiation through expressing RANKL/OPG cytokines. Recent studies have established that chondrocytes also express RANKL/OPG and support osteoclast formation. Till now, the in vivo function of chondrocyte-produced OPG in osteoclast formation and postnatal bone growth has not been directly investigated. In this study, chondrocyte-specific Opg transgenic mice were generated by using type II collagen promoter. The Col2-Opg transgenic mice showed delayed formation of secondary ossification center and localized increase of bone mass in proximal metaphysis of tibiae. TRAP staining showed that osteoclast numbers were reduced in both secondary ossification center and proximal metaphysis. This finding was further confirmed by in vitro chondrocyte/spleen cell co-culture assay. In contrast, the mineral apposition rates were not changed in Col2-Opg transgenic mice. TUNEL staining revealed more apoptotic hypertrophic chondrocytes in the growth plate of Col2-Opg mice. Flow cytometry analysis showed fewer RANK-expressing cells in the marrow of Col2a1-Opg mice, suggesting the role of OPG in blocking the differentiation of early mesenchymal progenitors into RANK-expressing pre-osteoclasts. Our results demonstrated that OPG expression in chondrocyte increases bone mass in the proximal metaphysis of tibiae through negative regulation of osteoclast formation.